Implikasi Hukum Pengaturan Ketenagakerjaan Terhadap Penggunaan Tenaga Kerja Luar Daerah Berkahlian Khusus pada Perusahaan Migas di Balikpapan - Jeslyn Josephine Seven Jon; Dudik Djaja Sidarta; Vallencia Nandya Paramitha; Fitri Ayuningtiyas (CV. Era Digital Nusantara, 2025)
Balikpapan City, as the national centre for the oil and gas industry, has a complex labour market dynamics due to the high demand for skilled workers. Balikpapan City Regulation No. 5 of 2023 on Labour Management serves as a legal instrument to regulate the proportion of local and non-local workers, particularly in the oil and gas sector, with the aim of enhancing the empowerment of local workers. This study aims to answer two main questions: (1) what forms of supervision and sanctions are imposed on oil and gas companies that fail to comply with the regional regulation, and (2) what are the legal implications for the use of non-local labour. The research method used is normative legal research with a statutory approach and a conceptual approach. Data was obtained from primary, secondary, and tertiary legal sources through literature review, then analysed qualitatively using deductive logic to connect legal norms and field practices. The research findings indicate that oversight of local regulation implementation still faces challenges, such as limited oversight resources, inconsistencies between regional and national regulations, and low reporting consistency by companies. The sanctions stipulated are administrative in nature, but their implementation has not been optimal. Legally, local regulations provide legitimacy for local governments to regulate local labour priorities, but they have the potential to cause conflicts with central regulations related to equal employment opportunities. In conclusion, the effectiveness of local regulations is highly dependent on strengthening supervision, harmonising regulations, and improving the competence of local workers through training and certification. Further research is recommended to examine an integrated oversight model that integrates the roles of government, companies, and society in ensuring the protection of local labour in strategic sectors.